Transition from ultra-enriched to ultra-depleted primary MORB melts in a single volcanic suite (Macquarie Island, SW Pacific): Implications for mantle source, melting process and plumbing system. (15th July 2016) - Husen, Anika; Kamenetsky, Vadim S.; Everard, John L.; Kamenetsky, Maya B.
Abstract: Compositional diversity of basalts forming the oceanic floor is attributed to a variety of factors such as mantle heterogeneities, melting conditions, mixing of individual melt batches, as well as fractionation and assimilation processes during magma ascent and emplacement. In this study the compositional range and origin of mid-ocean ridge basalts (MORB) is approached by petrological, mineralogical and geochemical studies of the Miocene Macquarie Island ophiolite, an uplifted part of the Macquarie Ridge at the boundary between the Australian and Pacific plates. In this study, earlier results on the enriched to ultra-enriched (La/Sm 1.4–7.9), isotopically homogeneous basaltic glasses are complemented by the compositions of olivine-phyric rocks, principal phenocrystic minerals and Cr-spinel hosted melt inclusions. Studied olivine, clinopyroxene and Cr-spinel phenocrysts are among the most primitive known for MORB (85–91 mol% forsterite in olivine, 81–91 Mg# in clinopyroxene, and 66–77 Mg# and 34–60 Cr# in spinel) and represent primary and near-primary compositions of their parental melts. Geochemical characteristics of the liquids parental to clinopyroxene (La/Sm 0.8–6.3) and Cr-spinel (La/Sm 0.4–5) partly overlap with those of the basaltic glasses, but also strongly advocate the role of depleted to ultra-depleted primary melts in the origin of the Macquarie Island porphyritic rocks. The trace element composition of olivine phenocrysts and the systematics of rare-earth elements in glasses, melt inclusions, and clinopyroxene provide evidence for a peridotitic composition of the source mantle. Our data supports the mechanism of fractional "dynamic" melting of a single mantle peridotite producing individual partial melt batches with continuously changing compositions from ultra-enriched towards ultra-depleted. The incipient enriched melt batches, represented by basaltic glasses in this study, may erupt without significant modification, whereas consecutively derived less enriched and depleted melt fractions are affected by mixing and crystal fractionation. Continuous melt generation, extraction, replenishment of the plumbing system, mixing and eruption of "integrated" melts lead to obliteration of the initially enriched geochemical characteristics and ultimately result in dominantly "normal", depleted MORB compositions.